The Relationship Between Family Support and Early Mobilization in Post-Cesarean Section (CS) Patients. - Inge Sintyadri Wahyu Sari; Patemah Patemah; Waifti Amalia (Media Husada Journal of Midwifery Science, 2026)
Caesarean section (CS) is a delivery process that involves making an incision in the uterus through the abdominal wall with the aim of minimising risks to the mother and foetus during the delivery process. Complications after surgery can prolong the length of hospitalisation and recovery. One factor affecting wound healing in post-C-section patients is early mobilisation. Early mobilisation is expected to improve blood supply, thereby affecting the speed of wound healing in mothers. The pain from the scar makes mothers reluctant to mobilise early. Family support is needed to encourage mothers to mobilise early after a caesarean section. The purpose of this study was to analyse the relationship between family support and early mobilisation in post-caesarean section patients at IRNA III RSUD dr. Saiful Anwar, East Java. The purpose of this study was to analyse the relationship between family support and early mobilisation in post-C-section patients. The methods used were interviews and questionnaires with a cross-sectional approach using questionnaires administered to 52 post-C-section mothers at IRNA III RSUD Dr. Saiful Anwar in East Java Province, where the level of support was high and early mobilisation was high. The results from 52 respondents showed that there was a significant relationship between family support and early mobilisation with a p-value of 0.039 and a correlation coefficient of 0.287. Thus, it can be concluded that the higher the family support, the higher the mobilisation.